Young Voters and Budget Deficits - Ole Henning Nyhus; Bjarne Strøm (Public Finance Review, 2026)
This study examines the impact of lowering the voting age from 18 to 16 in selected Norwegian municipalities in 2011. The quasi-experimental design reveals a reduction in net operating surplus by approximately NOK 600 (€60) per capita in affected local governments. This aligns with micro evidence suggesting that younger individuals have higher discount rates and greater propensity for risk-taking. Heterogeneity analyses suggest that the effect is more pronounced in municipalities with low party fragmentation, a high share of left-leaning representatives, and a high share of young representatives.